Cost-effectiveness of 2 + 1 dosing of 13-valent and 10-valent pneumococcal conjugate vaccines in Canada - Earnshaw, Stephanie R (BioMed Central, 2012)
BACKGROUND: Thirteen-valent pneumococcal conjugate vaccine (PCV13) and 10-valent pneumococcal conjugate vaccine (PCV10) are two recently approved vaccines for the active immunization against Streptococcus pneumoniae causing invasive pneumococcal disease in infants and children. PCV13 offers broader protection against Streptococcus pneumoniae; however, PCV10 offers potential protection against non-typeable Haemophilus influenza (NTHi). We examined public health and economic impacts of a PCV10 and PCV13 pediatric national immunization programs (NIPs) in Canada. METHODS: A decision-analytic model was developed to examine the costs and outcomes associated with PCV10 and PCV13 pediatric NIPs. The model followed individuals over the remainder of their lifetime. Recent disease incidence, serotype coverage, population data, percent vaccinated, costs, and utilities were obtained from the published literature. Direct and indirect effects were derived from 7-valent pneumococcal vaccine. Additional direct effect of 4% was attributed to PCV10 for moderate to severe acute otitis media to account for potential NTHi benefit. Annual number of disease cases and costs (2010 Canadian dollars) were presented. RESULTS: In Canada, PCV13 was estimated to prevent more cases of disease (49,340 when considering both direct and indirect effects and 7,466 when considering direct effects only) than PCV10. This translated to population gains of 258 to 13,828 more quality-adjusted life-years when vaccinating with PCV13 versus PCV10. Annual direct medical costs (including the cost of vaccination) were estimated to be reduced by $5.7 million to $132.8 million when vaccinating with PCV13. Thus, PCV13 dominated PCV10, and sensitivity analyses showed PCV13 to always be dominant or cost-effective versus PCV10. CONCLUSIONS: Considering the epidemiology of pneumococcal disease in Canada, PCV13 is shown to be a cost-saving immunization program because it provides substantial public health and economic benefits relative to PCV10.